2016
DOI: 10.1093/hmg/ddw035
|View full text |Cite
|
Sign up to set email alerts
|

ALS mouse model SOD1G93Adisplays early pathology of sensory small fibers associated to accumulation of a neurotoxic splice variant of peripherin

Abstract: Growing evidence suggests that amyotrophic lateral sclerosis (ALS) is a multisystem neurodegenerative disease that primarily affects motor neurons and, though less evidently, other neuronal systems. About 75% of sporadic and familial ALS patients show a subclinical degeneration of small-diameter fibers, as measured by loss of intraepidermal nerve fibers (IENFs), but the underlying biological causes are unknown. Small-diameter fibers are derived from small-diameter sensory neurons, located in dorsal root gangli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 56 publications
2
33
0
Order By: Relevance
“…The sparing of the IENF density proximal‐distal gradient in our patients indicates a non–length‐dependent neuropathic process which has been previously associated with a ganglionopathy rather than an axonopathy. The recent demonstration of a trigeminal small fibre loss through in vivo corneal confocal microscopy and the neuropathological evidence of damaged small diameter dorsal root ganglion cells in a G93A SOD1 murine model of ALS appear to be in agreement with this hypothesis. On the other hand there are experimental data in both patients and animal models supporting the hypothesis that the loss of IENF is due to a distal axonopathy.…”
Section: Discussionsupporting
confidence: 62%
“…The sparing of the IENF density proximal‐distal gradient in our patients indicates a non–length‐dependent neuropathic process which has been previously associated with a ganglionopathy rather than an axonopathy. The recent demonstration of a trigeminal small fibre loss through in vivo corneal confocal microscopy and the neuropathological evidence of damaged small diameter dorsal root ganglion cells in a G93A SOD1 murine model of ALS appear to be in agreement with this hypothesis. On the other hand there are experimental data in both patients and animal models supporting the hypothesis that the loss of IENF is due to a distal axonopathy.…”
Section: Discussionsupporting
confidence: 62%
“…These classes have been linked to a range of anatomical and physiological characteristics, such as cell soma size, presence of cell-specific protein markers, and electrophysiological properties, which can be used for reliable functional identification (26,29). Disparate sensory subtype sensitivities have previously been observed in mouse models of peripheral nerve disease (30,31). To see whether a particular kind of sensory neuron may be preferentially affected by the Gars C201R mutation, we divided the βIII-tubulin + cell bodies into small, medium, and large area neurons based on previously suggested criteria (32).…”
Section: Gars C201r/+ Dorsal Root Ganglion Cultures Have a Smaller Pementioning
confidence: 99%
“…A recent study in mutant SOD1 G93A mice, the most widely studied ALS mouse model, reported increased expression of the Peripherin isoform p56 in small DRG neurons, leading to an accumulation of non-assembled neurofilaments and a decrease in assembled neurofilaments (58). This may contribute to the degeneration of small DRG neurons and the loss of sensory axon endings in skin (58). Whether cytoskeletal defects also underlie the degeneration of large sensory axons (24,78) or dorsal root axons (18) remains to be determined.…”
Section: Discussionmentioning
confidence: 99%